Association Between Ultra-Processed Food Intake and All-Cause Mortality: A Systematic Review and Meta-Analysis. Issue 7 (1st March 2022) - Taneri, Petek Eylul; Wehrli, Faina; Roa-Díaz, Zayne M; Itodo, Oche Adam; Salvador, Dante; Raeisi-Dehkordi, Hamidreza; Bally, Lia; Minder, Beatrice; Kiefte-de Jong, Jessica C; Laine, Jessica E; Bano, Arjola; Glisic, Marija; et al.
Abstract: Consumption of ultra-processed foods (UPF) has increased worldwide during the last decades because they are hyperpalatable, cheap, and ready-to-consume products. However, uncertainty exists about their impact on health. We conducted a systematic review and meta-analysis evaluating the association of UPF consumption with all-cause mortality risk. Five bibliographic databases were searched for relevant studies. Random effects models were used to calculate pooled relative risks (RRs) and 95% confidence intervals (CIs). Of 6, 951 unique citations, 40 unique prospective cohort studies comprising 5, 750, 133 individuals were included; publication dates ranged from 1984 to 2021. Compared with low consumption, highest consumption of UPF (RR = 1.29, 95% CI: 1.17, 1.42), sugar-sweetened beverages (RR = 1.11, 95% CI, 1.04, 1.18), artificially sweetened beverages (RR = 1.14, 95% CI, 1.05, 1.22), and processed meat/red meat (RR = 1.15, 95% CI, 1.10, 1.21) were significantly associated with increased risk of mortality. However, breakfast cereals were associated with a lower mortality risk (RR = 0.85, 95% CI, 0.79, 0.92). This meta-analysis suggests that high consumption of UPF, sugar-sweetened beverages, artificially sweetened beverages, processed meat, and processed red meat might increase all-cause mortality, while breakfast cereals might decrease it. Future studies are needed to address lack of standardized methods in UPF categorization.